Digital Era’s Education and Aplication in Higher Education - Nisaul Barokati Seliro Wangi; M. Hafidh Nashrullah; Muh Barid Nizarudin Wajdi (STAI Miftahul Ula Nganjuk, 2018)
In the current digital era, education is in the age of knowledge (knowledge age) with the acceleration of an extraordinary increase in knowledge. The accelerated increase in knowledge is supported by the application of digital media and technology called information super highway. Education is becoming increasingly important to ensure students have learning skills, innovation, creativity, entrepreneurship as well as technology and information media skills and can work, and survive using life skills. 21st Century skills are (1) life and career skills, (2) learning and innovation skills, and (3) Information media and technology skills. These three skills are summarized in a scheme called rainbow 21st century knowledge skills / rainbow knowledge-skills rainbow. The scheme was adapted by the non-profit organization P21, which developed a 21st century educational framework throughout the world through the website www.p21.org based in the state of Tuscon, USA. Teacher professionalism improvement starts from individuals taking teacher training or equivalent to undergraduate education. At this stage, they are equipped with knowledge and skills in the fields of scientific substance and pedagogical substance. Teaching education must have a large portion in terms of pedagogical practice, which involves the ability to master the material, teaching, and technology. Higher education must now be able to facilitate all of these things and have the obligation to organize education in the direction needed.